Transforming Local Potential: The Jasper Stone Park Area as a Geographic Learning Resource - Ruli As'ari; Erni Mulyanie; Tineu Indrianeu; Mohammad Zohir Ahmad (Universitas Negeri Gorontalo, 2025)
This research seeks to enhance active learner participation and thinking skills geography by exploiting the geographic learning opportunities presented in the physical setting of Jasper Stone Park. The study was conducted using a field study mixed methods approach with qualitative and quantitative components using local observations, interviewing experts, and GIS spatial analysis. Jasper Stone Park was selected for this case study because the park's geological features and history are ethnically and environmentally diverse. The learning module developed included interactivity and therefore students were actively engaged in the material. The results prove that students’ comprehension of geographical concepts as well as critical thinking skills are deepened. The research highlights the effectiveness of the incorporated local materials as resources of instruction and suggests a new direction of interdisciplinary curriculum and educational policy design. Moreover, the results justify the incorporation of local materials into geography lessons and make a case for the application of this strategy in other geographical areas. Future research could investigate the long-term impact of the developed learning module on students' geographical understanding and critical thinking skills.